The psychosocial experience of adolescents with haematological malignancies in Jordan: an interpretive phenomenological analysis study - Omari, O.; Wynaden, Dianne (Hindawi Publishing Corporation, 2013)
The qualitative research method of interpretive phenomenological analysis was used to explore the lived experience of 14 Jordanian adolescents with haematological malignancies. They were admitted to two hospitals in Jordan and were interviewed for this study twice during the first six months after receiving their diagnosis. The results of this study revealed three themes: (1) Being in hospital, (2) The changing self, and (3) Fearing the unknown. When the participants were hospitalised due to their illness they were removed from their families and friends and prevented from engaging in their normal daily routine. Participants also reported receiving limited emotional and psychological support from health team members during hospitalisation. From the onset of cancer treatments, the bio-psychosocial side effects of the chemotherapy became one of the most distressing factors for participants affecting all aspects of their life and generated uncertainty about their future. The findings add to existing understanding of the lived experiences of cancer patients and in particular Jordanian adolescents. They provide a valuable insight for clinicians into improvements in service delivery to this group of patients.